Characterizing complication risk from multisite, intermittent transfusions for the treatment of sickle cell disease. Issue 10 (18th July 2019) - Tang, Amy; Branscomb, Jane; Zhou, Mei; Snyder, Angela; Eckman, James
Abstract: Blood transfusions are indicated for some acute complications of sickle cell disease (SCD). To characterize the SCD population at increased risk of transfusion‐associated complications, Georgia hospital discharge data were used to estimate the frequency of intermittent transfusions and the proportion of patients receiving them at multiple institutions. Ten years of data (2007‐2016) showed almost 19% of patients with SCD (1585/8529) received transfusions at more than one hospital. The likelihood of multisite transfusions increased from ages 18 through 40 and with the number of transfusions received. The results support the need to track and share transfusion histories in order to reduce complication risks.